True and False Realism. The ‘Machiavelli-Problem’ in Max Scheler and Romano Guardini - Allodi, Leonardo (Acta Philosophica, 2004)
The philosophies of Max Scheler and Romano Guardini are simultaneously both far apart and closely bound. The analytical and critical aim of this study is to examine this distance and closeness beginning with the so-called “Machiavelli-problem”, demonstrating that “overcoming machiavellianism” remains the “unresolved problem” of our times (A. Del Noce) and that a radical separation between politics and morals stems from a false realism. This same separation is found in the anthropology of self-immanence that both Scheler and Guardini consider at the base of that school of modern thought that leads to nihilism and contemporary relativism. In his most controversial period of thought, Max Scheler discussed the problem of peace and its historic feasibility in a systematic study, which is examined in depth in this work, on the relationship between morals and politics. Scheler’s analysis of the monistic and dualistic solutions appears particularly relevant if considered within the framework of a critique linking the questions of machiavellianism to the “common ideological denominator” of the present day, that is relativism. Scheler and Guardini reveal the importance and at the same time the partiality of Machiavelli’s realism. Guardini’s “philosophy of polar opposition” in particular appears to offer to the problem of political realism the pars construens that Scheler lacks. Only the philosophy of concrete living, which Guardini develops into a philosophy of opposition, offers a means of overcoming the limits of Machiavelli’s realism. These limits are partially the same as Scheler’s theory of the “impotency of the spirit”.